The effects of levosimendan in patients undergoing transcatheter aortic valve replacement- a retrospective analysis - Zhao, Zhenyan; Meng, Zhen; Song, Guangyuan; Wang, Chunrong; Shi, Sheng; Zhao, Jie; Zhang, Hongliang; Wang, Moyang; Niu, Guannan; Zhou, Zheng; Wang, Jianhui; Wu, Yongjian (Frontiers in Pharmacology, 2022)
Background: Aortic stenosis (AS) increases left ventricular afterload, leading to cardiac damage and heart failure (HF). Transcatheter aortic valve replacement (TAVR) is an effective therapy for AS. No inotropic agents including levosimendan have been evaluated in patients undergoing TAVR. Methods: A total of 285 patients underwent TAVR between 2014 and 2019; 210 were included in the matched analysis and 105 received 0.1 μg/kg body weight/min levosimendan immediately after the prosthesis had been successfully implanted. Medical history, laboratory tests, and echocardiography results were analyzed. Endpoints including 2-year all-cause mortality, stroke, or HF-related hospitalization, and a combination of the above were analyzed by Cox proportional hazard models. Results: The levosimendan group had no difference in 2-year mortality compared with the control group (hazard ratio [HR]: 0.603, 95% confidence interval [CI]: 0.197–1.844; P = 0.375). However, levosimendan reduced stroke or HF-related hospitalization (HR: 0.346; 95% CI: 0.135–0.884; P = 0.027) and the combined endpoint (HR: 0.459, 95% CI:0.215–0.980; P = 0.044). After adjusting for multiple variants, levosimendan still reduced stroke or HF-related hospitalization (HR: 0.346, 95% CI: 0.134–0.944; P = 0.038). Conclusion: Prophylactic levosimendan administration immediately after valve implantation in patients undergoing TAVR can reduce stroke or HF-related hospitalization but does not lower all-cause mortality.